Dampak Program Pemberdayaan Petani Melalui Sekolah Lapangan di Desa Bonorejo Kecamatan Gayam Kabupaten Bojonegoro - Khairunnisa, Hasna Sausan; Lestari, Eny; Widiyanti, Emi (Universitas Sebelas Maret, 2025)
The field school in Bonorejo Village has been implemented since 2020, initiated by ExxonMobil Cepu Limited (EMCL) in collaboration with the Bendera Nusantara Foundation (FIELD) as part of their Corporate Social Responsibility (CSR) program. A challenge faced by the field school in Bonorejo Village is the disparity in activity levels between farmers who have been participating since the beginning and those who have recently joined. This study aims to analyze the empowerment process of farmers in the field school in Bonorejo Village. Informants were determined using purposive and snowball sampling techniques, with a total of 10 informants. Data collection was conducted through observation, in-depth interviews, and documentation, followed by analysis using data collection, reduction, presentation, and conclusion drawing. Data validity was ensured through source, method, and technique triangulation. The results of the study show that the impact of empowerment consists of economic, behavioral, and social aspects. The economic impact is evident in the reduction of agricultural production costs; behavioral impact includes improved knowledge, attitudes, and skills, while the social impact is reflected in the increased social awareness due to friendships within the group, the emergence of mutual cooperation, helping behaviors, and expansion of farmers’ networks. However, these social interactions also have a negative impact, namely the emergence of inequality among field school participants. Farmers participating in the agricultural field school are expected to be more active and increase self-motivation in attending regular meetings.